Anti-Stress Activity (in-vivo) of Multi Herbal Capsule-Trasina® in Experimental Murine Model - Darbar, Soumendra Darbar; Saha, Srimoyee; Chattopadhyay, Shyamaprasad; Chattapadhyay, Atiskumar (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: In this modern era, stress has become a developing devil of human life.To maintain the healthy lifestyle measures adopted for smooth livelihood, stressshould be kept under control. Objective: The main aim and objective of the study was to find out the antistress activity of a multi herbal capsule Trasina® against anoxia stress tolerance, chemical induced stress, swimming endurance stress and immobilisation stress models inswiss albino mice. Methods: Trasina® was screened for its antistress activity at 50 mg/kg, 100 mg/kg, 200 mg/kg, p.o. doses and diazepam was applied as reference standard drug at 2 mg/kg i.p. dose.Anoxia stress tolerance time, number of writhes, immobility time, organs weight of animals and estimating biochemical parameters such as glucose, cholesterol, blood urea nitrogen (BUN) along with triglyceride were measured to evaluate antistress activity of the formulation. Results: Administration of Trasina® showed significant increases in anoxia stress tolerance time and significant decreases in number of writhes and immobility time in mice as compared with control untreated animals. In immobilisation stress model we observed that treatment with Trasina® significantly reduced glucose, cholesterol and blood urea nitrogen (BUN) and triglyceride levels. Moreover in stressful condition liver and adrenal gland weight were significantly increased whereas spleen weight was significantly decreased. Treatment with Trasina® maintained the normal organs weight as compared with stressful group. Conclusion: In conclusion it clearly showed that Trasina® possessed significant antistress activity and maintain normal homeostasis.